Investigating the effect of macrocycle size in anion templated imidazolium-based interpenetrated and interlocked assemblies. - Spence, G; White, N; Beer, P (2012)
The effect of varying the size of the macrocycle component on the formation of anion templated imidazolium interpenetrated assemblies is investigated. Two different approaches to reducing the macrocycle size are undertaken and the stabilities of the resulting pseudorotaxanes incorporating substituted imidazolium threading components studied using (1)H NMR spectroscopy. Novel imidazolium axle containing interlocked rotaxane host structures are synthesised using chloride anion templated amide condensation and 'stoppering' methods, and the anion recognition properties of the 'stoppered' rotaxane investigated.